Psycholinguistic representation of individual traumatic memory in the context of social and political ambiguity - Zasiekina, Larysa (Lesya Ukrainka Eastern European National University, 2014)
The paper focuses on a psycholinguistic study of individual traumatic memory. Among psycholinguistic tools of the research are psychographological analysis, propositional analysis, and frame analysis. The results of psychographological analysis revealed differences between psycholinguistic representations of traumatic events as compared to psycholinguistic representation of neutral events in norm for written speech. Higher psychographological indices in representation of traumatic events show the emotional lability (high sentence length), low awareness and meaningfulness of the event (high quotient of logical coherence), and low motivation (small number of words in the narratives). Frame analysis allowed revealing distribution of traumatic events in the context of political and social ambiguity. Propositional analysis showed distribution of propositional elements in the narration of traumatic events, which express the meaning of traumatic events in a person’s life (attitude); significance of external circumstances in the awareness of the traumatic event (external object); the main participants of the traumatic event (external argument); the narrator and his/her role in the traumatic event (internal argument); low importance of localization and chronological order of the traumatic event (context); the secondary (passive) role of narrator in the traumatic event and emphasizing the importance of the external circumstances (internal objects). The results of T-test show the differences in psycholinguistic representation of traumatic memory between two samples: respondents without PTSD (95 people) and respondents with PTSD and tendencies to PTDS (111 people). The narrators of the second sample (with PTSD) have higher indices of norm deviations in psychographological analysis, a higher percent of the attitude and internal argument in the predicate in propositional analysis, lower variety of frame clusters of traumatic events than narrators of the first sample (without PTSD).
Keywords: traumatic memory; post-traumatic stress disorder; psycholinguistic representation of traumatic memory; psychographological analysis; propositional analysis; frame analysis